Assessing the Response to Inhaled Albuterol by Monitoring Patient Effort-Related Trends With a Servo-I Ventilator in Neurally Adjusted Ventilatory Assist Mode: A Case Presentation. (December 2015) - Snow, Timothy Matthew; Brinck, Matthew J.
Abstract : Background: Infants with chronic lung disease tend to be difficult to care for due to the heterogeneous nature of both their disease and the treatments required. Multiple types of medications, treatments, and nursing interventions are often needed to attain clinical success, and it is frequently difficult to discern which are effective versus the ones that offer no benefit. This article presents a case study that chronicles the care of an infant with chronic lung disease treated with albuterol. An innovative form of ventilation with monitoring of the electrical activity of the diaphragm with a special sensor-embedded catheter is used to assess the effectiveness of albuterol administration. Purpose: This case study presents the monitoring of the effectiveness of albuterol in an infant with chronic lung disease measuring the electrical activity of the diaphragm catheter (Edi) and the various monitoring systems on the Servo-i ventilator in Neurally Adjusted Ventilatory Assist (NAVA) Mode. Case Findings/Results: The clinicians followed various respiratory trends monitored by the Servo-i ventilator after albuterol dosing to document the clinical utility of using albuterol in this infant. The monitoring provided by NAVA showed an improvement in both lung mechanics and clinical condition immediately after albuterol administration. Implications for Practice: The infant had a positive response to albuterol dosing that subsequently led to reduced length of stay, reduced costs, and reduced family anxiety. This type of monitoring could help nurses and clinicians discern whether a given treatment or medication was effective. Implications for Research: This method of clinical monitoring could provide a means to assess clinical utility of respiratory medications, treatments, and nursing interventions in certain populations of neonates and infants. The impact of objective monitoring on required sedation, weight gain, ventilator days, length of hospitalization, and overall hospital costs are other possible areas for future research.